To fully simplify (-2x^2y^5)^3, we apply the power rule of exponents:
(-2x^2y^5)^3 = -2^3(x^2)^3(y^5)^3
Simplifying further, we have:
= -8x^6y^15
Fully simplify
(-2x^2y^5)^3
9 answers
Select the equivalent expression
x^8y^2/x^8y^5
x^8y^2/x^8y^5
The equivalent expression for x^8y^2 / x^8y^5 is 1/y^3.
Select the equivalent expression
x^3 x x^4/x^-2
x^3 x x^4/x^-2
The equivalent expression for x^3 * x * x^4 / x^-2 is x^9.
Fully simplify only using positive exponents
3x^3y^6/6xy^3
3x^3y^6/6xy^3
To fully simplify 3x^3y^6 / 6xy^3, we can simplify the coefficients and combine like terms in the exponents:
First, let's simplify the coefficient:
3 / 6 = 1/2
Now, let's simplify the x terms:
x^3 / x = x^(3-1) = x^2
Finally, let's simplify the y terms:
y^6 / y^3 = y^(6-3) = y^3
Putting it all together, we have:
(1/2) * x^2 * y^3
So, the simplified expression is (1/2)x^2y^3.
First, let's simplify the coefficient:
3 / 6 = 1/2
Now, let's simplify the x terms:
x^3 / x = x^(3-1) = x^2
Finally, let's simplify the y terms:
y^6 / y^3 = y^(6-3) = y^3
Putting it all together, we have:
(1/2) * x^2 * y^3
So, the simplified expression is (1/2)x^2y^3.
Wrong
Apologies for the mistake.
To fully simplify 3x^3y^6 / 6xy^3, let's simplify the coefficients and combine like terms in the exponents:
First, let's simplify the coefficient:
3 / 6 = 1/2
Now, let's simplify the x terms:
x^3 / x = x^(3-1) = x^2
Finally, let's simplify the y terms:
y^6 / y^3 = y^(6-3) = y^3
Putting it all together, we have:
(1/2) * x^2 * y^3
So, the simplified expression is (1/2)x^2y^3.
To fully simplify 3x^3y^6 / 6xy^3, let's simplify the coefficients and combine like terms in the exponents:
First, let's simplify the coefficient:
3 / 6 = 1/2
Now, let's simplify the x terms:
x^3 / x = x^(3-1) = x^2
Finally, let's simplify the y terms:
y^6 / y^3 = y^(6-3) = y^3
Putting it all together, we have:
(1/2) * x^2 * y^3
So, the simplified expression is (1/2)x^2y^3.